Extracellular vesicles derived from mesenchymal stem cells alleviate neuroinflammation and mechanical allodynia in interstitial cystitis rats by inhibiting NLRP3 inflammasome activation - Chi Zhang; Yong Huang; Fubing Ouyang; Minzhi Su; Wenbiao Li; Jialiang Chen; Hengjun Xiao; Xiangfu Zhou; Bolong Liu (Journal of Neuroinflammation, 2022)
Abstract Background Neuroinflammation in spinal dorsal horn (SDH) plays an important role in the pathogenesis of interstitial cystitis/bladder pain syndrome (IC/BPS). Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) exert potent anti-inflammatory activities in the treatment of various diseases. This study aimed to determine the therapeutic effects of MSC-EVs on IC and furtherly investigate the potential mechanism to attenuate neuroinflammation. Methods Female IC rat model was established by intraperitoneal injection of cyclophosphamide (50 mg/kg, every 3 days for 3 doses). Inhibition of NLRP3 inflammasome was performed by intraperitoneal injection of MCC950 (10 mg/kg). MSC-EVs were isolated from the culture supernatants of human umbilical cord derived MSCs using ultracentrifugation, and then injected intrathecally into IC rats (20 μg in 10 μl PBS, every other day for 3 doses). Suprapubic mechanical allodynia was assessed using up-down method with von Frey filaments, and micturition frequency was examined by urodynamics. The expression of NLRP3 inflammasome components (NLRP3 and Caspase-1), glial cell markers (IBA-1 and GFAP), proinflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-18) and TLR4/NF-κB signal pathway (TLR4, p65 NK-κB and phospho-p65 NK-κB) in L6–S1 SDH was measured by Western blot analysis. The cellular localization of NLRP3 in SDH was detected using immunofluorescence co-staining. Results NLRP3 inflammasome was activated in neurons in SDH of IC rats. NLRP3 inflammasome activation contributed to activation of glial cells and process of spinal neuroinflammation in IC rats, and was related to suprapubic mechanical allodynia and frequent micturition. Intrathecal injection of MSC-EVs alleviated suprapubic mechanical allodynia and frequent micturition in IC rats, restrained activation of glial cells and attenuated neuroinflammation in SDH. In addition, MSC-EV treatment significantly inhibited activation of both NLRP3 inflammasomes and TLR4/NF-κB signal pathway. Conclusions NLRP3 inflammasome activation is involved in the neuroinflammation of IC. Intrathecal injection of MSC-EVs alleviates neuroinflammation and mechanical allodynia in IC by inhibiting the activation of NLRP3 inflammasome, and TLR4/NF-κB signal pathway may be the potential regulatory target.